2016
DOI: 10.3748/wjg.v22.i37.8406
|View full text |Cite
|
Sign up to set email alerts
|

Impact of hepatitis C virus core mutations on the response to interferon-based treatment in chronic hepatitis C

Abstract: AIMTo determine whether hepatitis C virus (HCV) core substitutions play a role in the response to interferon-based treatment in Caucasian patients.METHODSOne hundred eight HCV chronically infected patients initiating treatment with pegylated IFN plus ribavirin for 48 wk were tested for baseline substitutions at codons 70 and 91 of the viral core protein (BigDye Terminator vers.3.1, Applied Biosystems,) and for genetic polymorphisms in host IL28B gene rs12979860 (Custom TaqMan 5' allelic discrimination assay; A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 36 publications
0
10
0
1
Order By: Relevance
“…The meticulous biological pathways emphasizing the IL-28B gene SNP association with treatment response and viral clearance remain mysterious. Studies investigated IL28B polymorphism revealed that IL-28B polymorphism variants genotypes are linked with endogenous activation of host innate immunity (Sultana et al, 2016). As host innate immune mechanisms including IFN-γ control viral infection (Ibrahim et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The meticulous biological pathways emphasizing the IL-28B gene SNP association with treatment response and viral clearance remain mysterious. Studies investigated IL28B polymorphism revealed that IL-28B polymorphism variants genotypes are linked with endogenous activation of host innate immunity (Sultana et al, 2016). As host innate immune mechanisms including IFN-γ control viral infection (Ibrahim et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The presence of substitutions R to Q/H in aa position 70 of the nucleocapsid (core) of HCV 1b can help distinguish patients who can still benefit from the affordable IFN-based therapy from those who do not respond and are at an increased risk of HCC development [ 17 , 22 , 25 , 32 38 ]. There are also indications of the clinical significance of L to M substitution in aa position 91 of HCV 1b, although less well defined [ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“… Table S1: presentation by HLA I alleles of 9-mer peptide variants derived from the region between aa 62 and 78 of the nucleocapsid (core) of HCV 1b encompassing aa 70, predicted using EPISPOT tool ( http://bio.med.ucm.es/episopt.html ; EPISPOT [ 25 ]). Nine amino acid long peptides were chosen based on the consensus amino acid sequence of nucleocapsid (core) protein of HCV 1b variants isolated in the Russian Federation.…”
Section: Supplementary Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Forty-four 1b subtype HCV chronically infected Caucasian patients unexposed to any antiviral therapy were selected for study. Viral subtyping was assessed elsewhere by sequencing a fragment of core region (17). The study was approved by the Bioethics Committee of Cantacuzino National Medico-Military Institute for Research and Development and conducted in accordance with the ethical principles stated in the Declaration of Helsinki.…”
Section: Study Lotmentioning
confidence: 99%